(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2018)
This article deals with the impact of corporate governance on the performance of FMCG industries. FMCG product touches every aspects of human life. These products are frequently consumed by all sections of the society and a considerable portion of their income is spent on these goods. Apart from this, the sector is one of the important contributors of the Indian economy. Every company needs a set of processes, which may include rules and practices for direction and control. Such processes are often referred to as Corporate Governance (CG). Like any other governance, CG essentially is associated with balancing expectations of stakeholders. In our paper, we present the study on the similarities and the differences of the good Governance practices between the various companies under the sector of Fast Moving Consumer Goods (FMCG) sector.